Development of Nail Art Tutorial Video on Manicure Pedicure Courses - Hidayah, Nurul; M. , Sukardjo; Situmorang, Robinson (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this researcher is to develop video tutorial media for nail art learning on manicure pedicure courses. The method in this study is research and development of the ADDIE model. In terms of the material tested by panelists showing progressive results after the revised learning video tutorial. In terms of assessment test results received worthiness with a percentage of 80% to 90%. In terms of the assessment of the feasibility of the media tested by panelists showing progressive results after the revised nail art video tutorial. The first test results received worthiness with a percentage of 83% to 93%. The final result shows the achievement of the feasibility of all aspects of the indicator. Based on these results, it can be concluded that the nail art tutorial video has been very feasible and can be used as an alternative to learning because the media displayed is in accordance with good learning media indicators. On the assessment of 30 students who used nail art video tutorials, the feasibility of the media after the revision showed very progressive or increased results. The results of the first feasibility test of learning video media scored with a presentation of 82% to 91%. The nail art tutorial video has fulfilled various aspects of the characteristics or requirements of a good learning medium and is considered a very good medium or very feasible to be an alternative source of learning.